Late‐occurring infections in a contemporary cohort of hematopoietic cell transplantation survivors. (9th April 2021) - Sy, Andrew; Chanson, Dayana; Berano Teh, Jennifer; Wong, Florence L.; Nakamura, Ryotaro; Dadwal, Sanjeet; Armenian, Saro H.
Abstract: Background: There is a paucity of studies describing the incidence and risk factors for late‐occurring (≥1 year) infectious complications in contemporary survivors of hematopoietic cell transplantation (HCT). Methods: This was a retrospective cohort study of 641 1‐year survivors of HCT, transplanted between 2010 and 2013 as adults, and in remission from their primary disease. Standardized definitions were used to characterize viral, fungal, and bacterial infections. Cumulative incidence of infections was calculated, with relapse/progression considered as a competing risk event. Fine‐Gray subdistribution hazard ratio estimates and 95% confidence intervals (CI) were obtained, adjusted for relevant covariates. Results: Median age at HCT was 55.2 years (range 18.1–78.1 years); 54.0% were survivors of allogeneic HCT. The 5‐year cumulative incidence of a late‐occurring infection for the entire cohort was 31.6%; the incidence of polymicrobial (≥2) infections was 10.1%. In survivors who developed at least one infection, the 5‐year incidence of a subsequent infection was 45.3%. Among allogeneic HCT survivors, patients with acute lymphoblastic (HR = 1.82 95% CI [1.12–2.96]) or myeloid (HR = 1.50 95% CI [1.02–2.20]) leukemia, and those with an elevated HCT‐Comorbidity index score (HR = 1.09 95% CI [1.01–1.17]) were more likely to develop late‐occurring infections; there was an incremental risk associated with severity of graft versus host disease (GVHD) at 1‐year post‐HCT (mild: HR = 2.17, 95% CI [1.09–4.33]; moderate/severe: HR = 3.78, 95% CI [1.90–7.53]; reference: no GVHD). Conclusions: The burden of late‐occurring infections in HCT survivors is substantial, and there are important patient‐ and HCT‐related modifiers of risk over time. These findings may help guide personalized screening and prevention strategies to improve outcomes after HCT. Abstract : Highlights the high burden of late‐occurring infections by GVHD status at 1 year post‐HCT—a time point that typically corresponds to survivors transitioning away from the specialized HCT center to the community setting.